Tanggungjawab Dan Keterbukaan Dalam Laporan Keuangan Pada Lembaga Pengelola Zakat: (Studi Perbandingan Antara Badan Amil Zakat Dan Lembaga Amil Zakat Di Kota Medan) - D, Aswin Fahmi; Arief, 2Muhammad; Purnami, Suri; Nst, Armin Rahmansyah; Siregar, Saparuddin; Julianti Nasution, Yenni Samri (AGHNIYA : Jurnal Ekonomi Islam, 2024)
This study attempts to observe the implementation of transparency and accountability in OPZ by comparing two OPZs that have different management bases. Therefore, BAZNAS Medan City and Lazismu Medan City were chosen as the subjects of this study. This study aims to conduct a specific and measurable comparative study between BAZNAZ Medan City and Lazismu in Medan City with a focus on Accountability Indicators, Analyzing how well both institutions present financial reports, including reports on the use of funds, audits, and monitoring mechanisms. Then Transparency Indicators to Measure the level of openness of information to the public, such as accessibility of financial reports, use of social media, and community involvement in the management process, then Public Perception, Using a survey to measure the level of public trust in BAZ and LAZ, as well as the factors that influence their decisions in distributing zakat. This study is expected to provide clear and measurable insights into the practice of accountability and transparency of financial reporting in zakat management organizations in Medan City.